1952
DOI: 10.6028/jres.049.015
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of some simple sulfur-containing molecules

Abstract: The t hermodynamic functions ( F o-f1~) / T, ( HO -H~) / T, So ( Ho-Tl~) , and C; are calculated to high temperatures for gaseous sulfur (mon atomic and di ato mic) , sulfur monoxide, s ulfur dioxide, sulfur trioxide, and hydroge n sulfide from molecular and spectroscopic data. Values of the heats of formation of the various ato mic and molec uiar species are selected from published experimental data, and certain industrially importa ntequ ilibria are calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
3

Year Published

1962
1962
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 19 publications
1
22
0
3
Order By: Relevance
“…[7] is still valid in stack-gas compositions containing oxygen in concentrations up to 5%. [7] is still valid in stack-gas compositions containing oxygen in concentrations up to 5%.…”
Section: Results Of Tests On the Compensating Device--tomentioning
confidence: 99%
See 1 more Smart Citation
“…[7] is still valid in stack-gas compositions containing oxygen in concentrations up to 5%. [7] is still valid in stack-gas compositions containing oxygen in concentrations up to 5%.…”
Section: Results Of Tests On the Compensating Device--tomentioning
confidence: 99%
“…It was observed that mixtures with a low CO content, for example 1O0 ppm SO2 in 5% CO in CO2 (Po2 ~ 10 -16 atm at 815~ circulating in the detector has no effect on its operation when concentrations return to normal, although at such low partial pressures of oxygen, gaseous sulfur S2(g) coexists with the SO2 to a significant degree (7). No quarttitatively reproducible results have yet been obtained under such conditions as a function of the SO2 content.…”
Section: Results Of Tests On the Compensating Device--tomentioning
confidence: 99%
“…Энтальпия образования молекулы S 2 , опреде ленная из энергии диссоциации сероводорода в интервале температур 1362-1667 K, оказалась равной Δ f H = 30.8 ккал/моль [68]. Близкое зна чение (31.2 ккал/моль) получено при измерении парциального давления паров двухатомной серы в интервале температур 823-1273 K [46].…”
Section: обсуждение результатовunclassified
“…Именно величина Δ f H = 30.7 ккал/моль, полученная при высокой температуре, принята в качестве стандартной энтальпии образования молекулы S 2 при нормальных условиях [6], несмотря на то, что существование газообразной серы при комнат ной температуре в то время не было известно. По скольку экспериментальные измерения выпол нялись в равновесных условиях [46,68], то возни кает вопрос об электронном состоянии молекулы S 2 в высокотемпературной области. Как известно, любая система при равновесии должна находить g − 298°2 98°2 98°с я в термодинамически наиболее выгодном со стоянии, поэтому, очевидно, молекуле S 2 по умолчанию приписано основное триплетное со стояние, хотя ни в оригинальных работах [46,68], ни в справочной литературе [6] электронное со стояние этой молекулы не указано.…”
Section: обсуждение результатовunclassified
“…Zu diesen D aten gehören unter anderem die Standardentropien (*S°) und die Mol wärmen (Cp), die sich aus den Molekülstrukturen und den Normal schwingungen der betreffenden Spezies nach den Form eln der statistischen Thermodynamik [10] be rechnen lassen. F ü r Sö [11], S 7 [12] und Sg [13 -15] wurden solche Rechnungen bereits durchgeführt, nicht jedoch für größere und kleinere Moleküle (ausgenommen S 2 [16]), da von den meisten weder Sonderdruckanforderungen an Prof. Dr. R . Steudel, In stitu t für Anorganische und Analytische Chemie der Technischen U niversität Berlin, Sekr.…”
Section: Introductionunclassified